Selawat Nabi in The Construction of Local Sufis and Revivalists in Indonesia - Zetty Azizatun Ni'mah (Didaktika Religia, 2020)
This study aims to reveal the understanding of local Sufis and revivalists about Selawat Nabi.Â The two schools, if their ideological roots are traced, are different. But they both share the concept of Selawat Nabi which is believed to be the construct of understanding.Â This research is interesting, because local Sufis with theological revivalists (not sharia, which is ritual muamalah), still carry out the construct of thought.Â This is also a point of research significance.Â This research is a qualitative-descriptive literature review with a phenomenological approach.Â The result of this research isÂ that local Sufis state that the Prophet'sÂ selawatÂ is a medium to achieveÂ wusul to Allah accompanied by appreciation through the concept ofÂ opening,Â it will be acceptable because it is closely related to the formation of adab so that it is kept away from behavior that can harm oneself and others.Â The figure of the Messenger of Allah is to make him live in the soul by verbally reproducing selawat.Â The routine of reading selawat is a connection between the readers of selawat and the Prophet which is actualized in the behavior of imitating the Prophet's morals.Â Revivalists adhere to selawat ma'surat whose pronunciation is following the guidance of the Prophet.Â Saying selawat is not the main thing in loving the Prophet, but the most important thing is to make the Prophet's figure to live in the soul and have the morals of the Prophet.